Relationship Between Childhood Left-Behind Experience and Quality of Life Among Chinese University Freshmen: Place of Origin Matters - Li, Hai-Mei; Xu, Yan-Min; Zhong, Bao-Liang (Frontiers in Psychiatry, 2021)
Background: Childhood left-behind experience (LBE) has a long-term detrimental effect on the mental health of Chinese University students, but it remains unclear whether childhood LBE negatively impacts the quality of life (QOL) of University students and whether the LBE–QOL association differs between students of rural origin and students of urban origin. This study examined the LBE–QOL relationship and the interactive effect between LBE and place of origin on QOL among Chinese University freshmen. Methods: By using a two-stage random cluster sampling approach, a total of 5,033 freshmen were recruited from two comprehensive universities. The students completed an online, self-administered questionnaire that included sociodemographic variables, a 2-week physical morbidity assessment, and assessments of depressive symptoms, academic stress, and QOL. The Chinese six-item QOL scale was used to assess QOL. Multiple linear regression was used to test the independent LBE–QOL association and the interaction between LBE and place of origin. Results: Students with childhood LBE had significantly lower QOL scores than those without LBE (60.1 ± 13.1 vs. 64.3 ± 11.7, p < 0.001). After adjusting for the potential confounding effects of other sociodemographic variables, 2-week physical morbidity, depressive symptoms, and academic stress, childhood LBE was significantly associated with a lower QOL score (β: −3.022, p < 0.001) and the LBE–place of origin interaction was still significantly associated with the QOL score (β: −2.413, p < 0.001). Overall, compared to non-LBE, LBE was associated with a QOL score decrease of 5.93 among freshmen of urban origin and of 3.01 among freshmen of rural origin. Conclusion: In Chinese University freshmen, childhood LBE is independently associated with poor QOL, and the LBE–QOL association is greater among freshmen from urban backgrounds than among freshmen from rural backgrounds.